Precisely dated multidecadally resolved Asian summer monsoon dynamics 113.5–86.6 thousand years ago. (1st July 2016) - Jiang, Xiuyang; Wang, Xiaoyan; He, Yaoqi; Hu, Hsun-Ming; Li, Zhizhong; Spötl, Christoph; Shen, Chuan-Chou
Abstract: We present a new 230 Th-dated absolute chronology of Asian summer monsoon (ASM) variability from 113.5 to 86.6 kyr BP (before 1950 AD). This integrated multidecadally resolved record, based on 1435 oxygen isotope data and 46 230 Th dates with 2-sigma errors as low as ±0.3 kyr from three stalagmites collected in Sanxing Cave, southwestern China, can be a new reference for calibrating paleoclimate proxy sequences. The Sanxing δ 18 O record follows the 23 kyr precessional cycle of insolation and is punctuated by prominent millennial-scale oscillations of the Chinese Interstadials (CIS) 25 to 22, corresponding to Greenland Interstadials (GIS) 25 to 22. The onset of CIS 25, 24, 23 and 22 is dated to 113.1 ± 0.4, 108.1 ± 0.3, 103.7 ± 0.3 and 91.4 ± 0.6 kyr BP in the Sanxing record, respectively. The end of CIS 24 and CIS 22 is constrained to 105.5 ± 0.4 and 87.7 ± 0.3 kyr BP, respectively. A centennial-scale precursor event at 104.1 ± 0.3 kyr BP preceding CIS 23 is clearly registered. These events in the Sanxing record are synchronous with those identified in stalagmites from the European Alps (NALPS), except for the onset of GIS 25 and the end of GIS 22, and differ by up to 2.3 kyr from the corresponding ones in Greenland ice core records. The high degree of similarity of the δ 18 O records between Sanxing Cave and Greenland supports a Northern Hemisphere forcing of the ASM. The anti-phase relationship of δ 18 O records between Sanxing stalagmites and Antarctic ice cores suggests an additional ASM linkage to the Southern Hemisphere. Highlights: A record of multidecadally resolved Asian monsoon variability between 113.5 and 86.6 kyr BP. The first-time identification of GIS 23 precursor event in a continental archive of the Asian monsoon. Precisely dated stalagmite δ 18 O provide a promising reference for calibrating paleoclimate proxy sequences.